1998
DOI: 10.1021/om9709953
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of the Lewis Acid Tris(pentafluorophenyl)borane with a Phosphorus Ylide:  Competition between Adduct Formation and Electrophilic and Nucleophilic Aromatic Substitution Pathways

Abstract: Treatment of the phosphorus ylide Ph 3 PdCH 2 (2a) with B(C 6 F 5 ) 3 (1) yields the adduct Ph 3 P + -CH 2 -B(C 6 F 5 ) 3 -(3a), which was characterized by X-ray crystal structure analysis. The ylide Ph 3 PdCHPh (2b) reacts analogously with B(C 6 F 5 ) 3 at 0 °C to form Ph 3 P + -CHPh-B(C 6 F 5 ) 3 -(3b), but this adduct formation is reversible. Increasing the temperature leads to the formation of Ph 3 P + -CH 2 -(p-C 6 H 4 )-B(C 6 F 5 ) 3 -(4), which is formed by an electrophilic aromatic substitution reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
59
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 15 publications
12
59
0
5
Order By: Relevance
“…cyanide was attractive due to the remarkable "anion abstracting properties of this special boron compound". [29,30] The hypothesis involving nucleophilic attack of the alkene at the central cyanamide carbon atom was attractive since this is the typical site of nucleophile attack on cyanamides.…”
Section: Methodsmentioning
confidence: 99%
“…cyanide was attractive due to the remarkable "anion abstracting properties of this special boron compound". [29,30] The hypothesis involving nucleophilic attack of the alkene at the central cyanamide carbon atom was attractive since this is the typical site of nucleophile attack on cyanamides.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, it was suggested that pyridine attacks the carbon para to the carbocation, [100] although this report was subsequently disputed. [101] In 1998, Doering et al [102] described the reaction of the Lewis acid B(C 6 F 5 ) 3 , which is isoelectronic to the trityl cation, with the ylide Ph 3 PCHPh. It was shown that the classical Lewis adduct, (Ph 3 PCHPh)B(C 6 F 5 ) 3 , formed reversibly at room temperature and rearranged at higher temperature to effect attack at the para-position of one of the C 6 F 5 rings.…”
Section: Para-substitution Reactionsmentioning
confidence: 99%
“…[101] 1998 beschrieben Döring et al die Reaktion der Lewis-Säure B(C 6 F 5 ) 3 , die isoelektronisch zum Tritylkation ist, mit dem Phosphor-Ylid Ph 3 PCHPh. [102] Es konnte gezeigt werden, dass die Bildung des klassischen Lewis-Addukts (Ph 3 PCHPh)B-(C 6 F 5 ) 3 in diesem Fall reversibel ist. Bei erhöhter Temperatur findet über die Rückreaktion eine Umlagerung unter Angriff des Ylid-Nucleophils auf das para-Kohlenstoffatom eines C 6 F 5 -Rings statt.…”
Section: Para-substitutionenunclassified
“…Nachfolgende Fluoridübertragung auf das Boratom führt dabei zum zwitterionischen Phosphoniumboratsystem Ph 3 PCHPh(C 6 F 4 )BF(C 6 F 5 ) 2 (Schema 54). [102] Bei ähnlichen Reaktionen von Tritylboraten mit LewisDonoren konnte gezeigt werden, [103] dass sperrige Phosphine mit tBu-, iPr-oder Cy-Substituenten nicht das Carbokation angreifen, sondern unter nucleophiler Substitution am paraKohlenstoffatom des Arens zu den Salzen 140 oder 141 reagieren (Schema 55). [103] In der Folge konnte gezeigt werden, dass diese Reaktionsweise recht allgemeingültig ist.…”
Section: Para-substitutionenunclassified